1998
DOI: 10.1212/wnl.50.4.883
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of tissue plasminogen activator for acute ischemic stroke

Abstract: Tissue plasminogen activator (tPA) has been shown to improve 3-month outcome in stroke patients treated within 3 hours of symptom onset. The costs associated with this new treatment will be a factor in determining the extent of its utilization. Data from the NINDS rt-PA Stroke Trial and the medical literature were used to estimate the health and economic outcomes associated with using tPA in acute stroke patients. A Markov model was developed to estimate the costs per 1,000 patients eligible for treatment with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
317
1
5

Year Published

2002
2002
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 348 publications
(331 citation statements)
references
References 14 publications
8
317
1
5
Order By: Relevance
“…The conversion of the Ranking scale levels into a quality of life index was obtained according to the results of previous studies done by Fagan et al [20] and Pinto et al [21]. Scale level 0 was converted to 0.9, scale level 1 was converted to 0.68, scale level 2 was converted to 0.47, scale level 3 was converted to 0.2, scale level 4 was converted to 0.07, scale level 6 was converted to 0 and scale level 5 was converted to −0.02.…”
Section: Health Benefitsmentioning
confidence: 99%
“…The conversion of the Ranking scale levels into a quality of life index was obtained according to the results of previous studies done by Fagan et al [20] and Pinto et al [21]. Scale level 0 was converted to 0.9, scale level 1 was converted to 0.68, scale level 2 was converted to 0.47, scale level 3 was converted to 0.2, scale level 4 was converted to 0.07, scale level 6 was converted to 0 and scale level 5 was converted to −0.02.…”
Section: Health Benefitsmentioning
confidence: 99%
“…When studied in the North American healthcare system, thrombolysis was shown to be cost saving due to the reduction in rehabilitation and nursing home costs. 48 The only study conducted into the cost efficiency of thrombolysis use in the NHS, 49 however, concluded that although the benefits appeared promising, the estimates of effectiveness and cost effectiveness were imprecise. This imprecision resulted in a huge variability in outcomes, ranging from large cost savings under favourable assumptions to large expenditures using less favourable estimates.…”
Section: Cost Effectivenessmentioning
confidence: 99%
“…Cost-effectiveness studies concerning primary 4 and secondary prevention 5 , diagnostic testing 6 , thrombolysis [7][8][9][10][11][12][13][14][15] , rehabilitation 16 , management systems 17 and also the informal care costs of long-term care after stroke 18,19 have been published. Few studies have explored the cost-effectiveness of mechanical thrombectomy [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%